Procedures for standard evaluation and data management of advanced potato clones. Practical guide to assessing potato clones for drought tolerance under field conditions - Cabello, R.; Cevallos, D.; Souza, J. de; Gutiérrez, R.; Farfán, E.; Lozano, F.; Eyzaguirre, R.; Khan, A.; Schafleitner, R.; Bonierbale, Merideth W. (International Potato Center, 2020)
This protocol aims to aid in the design of field trials to characterize the performance of potatoes under drought stress, to understand the relationship of agro-morphological, physiological, and tuber traits with tolerance and susceptibility; and to identify the underlying genetics. Precise and accurate phenotyping of component traits are a prerequisite for proper genetic dissection, therefore, most of the methods recommended here are quantitative, to reduce subjectivity and increase genetic studies effectiveness. These are general guidelines that should be taken as recommendations to conduct drought trials, particularly in field, but could also be used in greenhouse or controlled-environment chambers. It should be noted that this protocol has not been intended for large germplasm screenings or in vitro screenings; therefore, the number of clones, the experimental design, the plant physiological stage at drought initiation, and types of evaluations depend solely on researcher’sspecific objectives. Specific formats for data collection with a minimum size of metadata, and defined trait dictionaries have been added in the International Potato Center’s Global Data Management System, where they can be analyzed using CIP’s user friendly analytical platform (HiDAP), which include a wide range of statistical functions; from basic descriptive statistics to multivariate analysis and selection of top performing clones for further studies and use in breeding programs.